Equine therapy interventions in improving language aspects of dyslexic children - Kunasegran, Kavenia; Subramaniam, Vijayaletchumy (University of Shanghai for Science and Technology, 2020)
Animal-assisted therapies are being widely acknowledged for improving the needs of children with various difficulties. One of the many animal-assisted therapies that are known to be beneficial includes equine therapy. The primary aim of this research was to study the improved language aspects of dyslexic children after undergoing five equine therapy interventions. The five equine therapy interventions include friendly introduction to horses, auditory comprehension, phonological awareness, sentence mastery and spelling ability. A randomised study was done by selecting 16 dyslexic children from Malaysia Dyslexia Association in carrying out equine therapy. Results from the study done proved that the dyslexic children chosen has demonstrated vast improvement in the following aspects of language, namely comprehension, phonological, sentence mastery and spelling. The general assumption of this study is that every equine therapy intervention has its own unique objective and outcome on dyslexic children. Further research is required in this domain to study the long-term effects of equine therapy in other areas of special need children.